Nutritional and industrial quality assessment of Spanish durum wheat commercial cultivars - Garcia-Calabres, Virginia; Andrade, Francisco; Tabbita, Facundo; Castilla, Alejandro; Sillero, Josefina Carmen; Hernandez-Espinosa, Nayelli; Ibba, Maria Itria; Guzman, Carlos; Alvarez, Juan B. (Wiley, 2025)
BACKGROUND Durum wheat is the raw material used to produce pasta, and its price is determined by grain physical characteristics, gluten strength and semolina yellowness. Gluten strength is mainly determined by high- and low-molecular-weight glutenin subunits (HMW-GS and LMW-GS). Semolina yellowness is determined by loci that control carotenoid content and lipoxygenase activity. Arabinoxylans are the major dietary fibre component within the durum wheat endosperm. Twelve durum wheat cultivars were grown in five locations over two cropping seasons. The objectives of this study were to determine the variability in the aforementioned traits; to assess the influence of genotype, environment and their interaction; and to determine the allelic variation of the main genes associated with gluten strength and semolina yellowness. RESULTS Grain physical characteristics were mainly determined by the environment. However, the genotype exerted a strong influence on gluten strength, semolina yellowness and arabinoxylan content. There was wide variation in all traits, but arabinoxylan content was limited. For HMW-GS the most common alleles were Glu-A1c and Glu-B1b, while for LMW-GS they were GLU-A3a, GLU-B3a and GLU-B2a. Regarding carotenoid synthesis genes, Psy-A1l, Psy-B1o, Pds-B1b and TdZds-A1.1 were the most frequent alleles; while Lpx-A3 UC1113 and Lpx-B1.1a were predominant for lipoxygenase genes. CONCLUSIONS Although the best alleles for gluten quality and yellow colour are present, they are not combined in a single cultivar, which limits the maximisation of overall quality. This study also highlights the importance of searching for arabinoxylan donors due to the limited genetic variability for this trait in commercial durum wheat cultivars.